Diagnostic value of chemiluminescence for urinary lipoarabinomannan antigen assay in active tuberculosis: insights from a retrospective study - Huang, Luyi; Niu, Yayan; Zhang, Li; Yang, Rong; Wu, Meiying (Frontiers in Cellular and Infection Microbiology, 2023)
This study aimed to assess the efficacy of chemiluminescence-based urinary lipoarabinomannan (LAM) antigen assay as a diagnostic tool for identifying active tuberculosis.A retrospective study was conducted on 166 Tuberculosis (TB), 22 Non-Tuberculous Mycobacteria (NTM), 69 Non-TB cases, and 73 healthy controls from Zhangjiagang First Peoples Hospital between July 2022 and November 2022. Clinical and laboratory data were collected, including urine samples for LAM antigen detection, sputum samples and pleural effusion for GeneXpert, TB-DNA, and culture.Results TB group exhibited a higher LAM positivity rate (P < 0.001). CD4 count and diabetes as independent factors influencing the diagnostic accuracy of LAM. The LAM assay showed a sensitivity of 50.6% and a specificity of 95.65%. Notably, LAM's sensitivity was superior to TB-DNA (50.60% vs.38.16%, P < 0.05). LAM's PTB detection rate was 51.7%, superior to TB-DNA (P = 0.047). Moreover, in EPTB cases, the LAM detection rate was 42.11%, surpassing Gene Xpert (P = 0.042), as well as exceeding the detection rates of TB-DNA and sputum culture.LAM antigen detection using chemiluminescence has demonstrated outstanding clinical diagnostic value for active TB, especially in the diagnosis of extrapulmonary TB. The convenience of sample collection in this diagnostic approach allows for widespread application in the clinical diagnosis of active tuberculosis, particularly in cases of EPTB and sputum-negative patients.